Improving the outcomes of kidney transplantation from deceased organ donors - Akhtar, MZ (2016)
This thesis sought to improve our understanding of how kidneys become injured as a consequence of organ donation, with the aim of improving the outcomes of transplantation. Every year, hundreds of patients on the waiting list die whilst awaiting a kidney transplant. With an ever-increasing demand for suitable organs, supply cannot keep up with the pressures on the transplant waiting list. As a consequence the transplant community are forced to use organs that previously would not have been considered suitable for transplant, including from older donors with additional comorbidities. This thesis aimed to develop an understanding as to how the kidney becomes injured during the donation process, identifying which key cellular homeostatic processes are disturbed as a consequence of donation. The thesis outlines the experimental development of rodent models of organ donation replicating the donation process for donation after brain death (DBD) and donation after circulatory death (DCD) donors and also the development of a kidney ischaemia reperfusion injury (IRI) model. Proteomics was subsequently used to identifying global protein alterations in the kidney as a consequence of brain death and ischemia reperfusion injury using bioinformatics tools to identify involvement of cellular pathways. The results indicated alterations in mitochondrial function and metabolic homeostasis occurring following brain death. Alterations in cellular metabolism and mitochondrial function were then confirmed using metabolomics and mitochondrial functional assays. I subsequently evaluated how alterations in cellular hypoxia and the hypoxia inducible factor system is altered in the brain dead organ donor kidney and aimed to target this system as a means of conditioning the brain dead organ donor to prevent mitochondrial and metabolic mediated injury to kidney cells following brain death. This involved exploring the role of prolyl hydroxylase inhibitors, including dimethyloxalylglycine, on mitochondrial function and whether this could be a therapeutic target in organ donation. This thesis provides important insights into the mechanism of injury of kidneys following brain death, providing evidence that even before procurement and preservation in the DBD donor alterations in mitochondrial function and metabolic homeostasis occur. I provide preliminary data on the use of prolyl hydroxylase inhibitors in altering mitochondrial function. I also outline my involvement in other ongoing projects in organ donation and machine perfusion that also aim to improve the outcomes of deceased donor kidney and liver transplantation.